Sedimental pollen records in the northern South China Sea and their paleoenvironmental significance. (January 2023) - Bandara, Gayan; Luo, Chuanxiu; Chen, Chixin; Xiang, Rong; Herath, Dileep B.; Yang, Zijie; Thilakanayaka, Vidusanka
Highlights: Pollen from sediments in Taiwan Strait originate from Taiwan and Southeastern China. Dominance of Pinus reveals a cool, wetter climate with decreasing sea level in MIS4. Dominance of herb and alpine conifers taxa signify a colder climate during LGM. Holocene is dominated by Pinus and ferns, denoting the climate was comparable to the present day. Abstract: Studies on the reconstruction of long-term climatic and vegetation dynamics around the northern South China Sea (SCS) are limited. Therefore, this study was conducted to get a clear understanding of the paleoenvironmental significance around the Taiwan Strait in northern SCS. The chronology was based on the accelerator mass spectrometry (AMS) 14 C dates of mixed planktonic foraminifera, then we compared and cross-validated the age–depth model based on the grain-size analysis and foraminifera data. Palynomorph data, including percentages and concentrations based on marine sediment cores (WQZK1, WQZK2, and WQZK3), were used to reconstruct the history of vegetation and climate changes and identify the provenance and transport mechanisms of pollen and spores. The findings indicated that fern spores dominated the interglacial period, suggesting intense summer monsoons during warm periods in marine isotope stages (MIS) 5–MIS 1. During MIS 5a, tropical and subtropical conifers with temperate components dominated, indicating the climate was comparatively warm at an increasing sea level. The lowest sea level subtly proved cooler and wetter climate, subsequently affecting a drastic increase of Pinus during MIS 4. Tropical and subtropical conifers dominated during the MIS 3, and the sea level increased comparatively to MIS 4, indicating warmer climate conditions. Pinus pollen and fern spores dominated MIS 1, implying that the paleoenvironment was comparable to the present day. Therefore, this study supports previous studies on the northern SCS region and suggests that a combination of pollen with other proxies provides a better understanding of vegetation and climatic dynamics in the past.